IĞDIR HALK EĞİTİM MERKEZİ: 2014’den 2024’e MÜZİK EĞİTİMİ SERÜVENİ - Mammadaliyeva, Mihriban; Aktaş, Menekşe (TURAN : stratejik arastirmalar merkezi, 2025)
This study aims to examine the music education conducted at the İgdir Public Education Center between the years 2014 and 2024, focusing on the structure, practices, and social impacts of the educational process. The primary data source of the research consists of structured interviews conducted with five instructors who provided music education at the center. The findings indicate that the music courses serve multifaceted functions, including personal development, social participation, cultural transmission, and preparation for professional music education. The fact that the Public Education Center courses are open to individuals of all ages without any age restrictions demonstrates the practical implementation of the principles of accessibility and inclusivity. Furthermore, the courses being offered free of charge help reduce socioeconomic barriers, thereby increasing access to cultural activities and strengthening social solidarity. However, participants highlighted issues such as declining demand and limited course variety, emphasizing the need for improvements in these areas. In conclusion, the research shows that the music education provided by the İgdir Public Education Center makes meaningful contributions to individuals’ artistic development and the cultural structure of society. It is recommended that future studies be supported by broader participant profiles and diverse data sources.